To what extent does infrastructure stock and quality influence the levels and volatility of capital flows - Alinsunurin, Jason P. (Animo Repository, 2014)
Recent empirical works have shown that a country's stock and quality infrastructure (transport, communication, power, water and sanitation) is highly correlated with economic growth, poverty reduction and other composite measures of socioeconomic development. While there has been recent work analyzing its linkages to sub-components of economic growth especially in consumption investments, export growth and spending, there are few empirical researches relating the volatility and levels of capital flows to the stock and quality of infrastructure quality. Using the 1960 to 2011 panel data from WDI, IFS and the Penn World Tables, we model capital flow in a generalized model of moments (GMM) framework. We formulate a synthetic index of infrastructure stock and quality using this principal components approach and perform robustness checks called Bayesian Model Averaging (BMA) to ascertain which specific among a set of infrastructure indicators may be included in the model. Lastly, we distinguish the effects between developing and developed countries, as well as between regions and groupings and perform simulation tests. We hypothesize that the influence of infrastructure to the levels and volatility of capital flows can be isolated from institutional human capital and other previously known determinants.